From Harm to Hope: Tackling Microplastics’ Perils with Recycling Innovation - Irene Dini; Andrea Mancusi; Serenella Seccia (Molecules, 2025)
This review examines how plastics break down into dangerous pollutants like microplastics, nanoplastics, and persistent organic pollutants (POPs) that can contaminate the environment, make their way into the human food chain, and provoke toxicological effects in humans. According to the reviewed literature, new biomarkers associated with their exposure should be identified, and new methods for detecting them in the environment and in food should be developed and validated. It would also be interesting to improve research on the interaction between micro- and nanoplastics and human cells, their impact on DNA, and their long-term health effects. Promoting sustainable practices and adherence to the 3R strategies (reduce, reuse, and recycle) to transform hazardous waste into valuable resources is crucial to protecting public health from dangerous contaminants as we wait on the development of new diagnostic methods and more stringent legislation.